ROUTLEDGE WORLD COMPANION TO POLISH LITERATURE - Bilczewski, Tomasz, 1978-; Bill, Stanley; Popiel, Magdalena ([S.l.] : ROUTLEDGE, 2021)
The Routledge World Companion to Polish Literature offers an introduction to Polish literature through thirty-three case studies, covering works from the Middle Ages up to the present day. Each chapter draws on a text or body of work, examining its historical context, as well as its international reception and position within world literature. The book presents a dual perspective on Polish literature, combining original readings of key texts with discussions of their two-way connections with other literatures across the globe. With a detailed introduction offering a narrative overview, the book is divided into six sections offering a chronological pathway through the material. Contributors from around the world examine the various cultural exchanges at play, with each chapter including: Definitions of key terms and brief overviews of historical and political events, literary eras, trends, movements, groups, and institutions for those new to the area Analysis and notes on translations, including their hidden dimensions and potential Textual focus on poetics, such as strategies of composition, style, and genre A range of historical, sociological, political, and economic contexts From medieval song through to the contemporary novel, this book offers an interpretive history of Polish literature, while also positioning its significance within world literature. The detailed introductions make it accessible to beginners in the area, while the original analysis and focused case studies will also be of interest to researchers.
Keywords: Polish literature -- History and criticism; Polish literature -- Appreciation; LITERARY CRITICISM / General; LITERARY CRITICISM / European / Eastern (see also Russian & Former Soviet Union)